BPMN pra GERAL, Business Process Models in a Citizen Language - Carvalho, Luiz Paulo; Cappelli, Claudia; Santoro, Flávia Maria (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Brazilian laws, such as the Law on Access to Information, mandate the transparency of public procedural information, in a clear, simple and understandable manner. However, the existent process-oriented citizen language and a BPMN translation method that would enable these requirements are still informal and unstructured. These problems have limited their use, culminating in a dependency on experts. This paper presents a framework with four components (notation, semantics, computer tool, and method) to merge, structure and complement the citizen process language, GERAL, and respective translation, in a guide dedicated to lay users in technical process modeling, called BPMN pra GERAL. The Design Science Research method conducted the formative research, around the engineering of an artifact with epistemological rigor and scientific assessment methods with both a qualitative and quantitative approach, involving four participants in a library at a public university. The results are positive, participants showed interest, perception and intention to use the guide in real cases; increased their awareness of the need for process transparency; and all participants used the solution effectively. This research contributes to transparency, information accessibility, business process modeling and understandability.